Ultrasound-Guided Peripheral Nerve Block as Post-Operative Management of Lower Abdominal Surgery in Ksatria Airlangga Floating Hospital - Setjaputra, Vina Lidya; Susianto , Steven Christian; Silitonga , Jessica Deborah; Kusumaningtyas , Maya Hapsari; I Putu Agni Rangga Githa; Atmaja, Robbi Tri; Wardhana, Burhan Mahendra Kusuma; Bandem, I Ketut Mega Purnayasa; Firdaus, Khildan Miftahul; Harianto, Agus (Indonesian Journal of Anesthesiology and Reanimation, 2024)
Introduction: Enhanced Recovery After Surgery (ERAS) implementation in remote areas by operating hospital ships is immensely helpful due to high patient turnover, reducing costs, and minimizing the effects of surgical stress. Utilization of regional anesthetics, namely ultrasound-guided Transversus Abdominis Plane (TAP) block or Quadratus Lumborum (QL) block, is applicable and beneficial in this setting. Objective: Due to the limited time, facilities, and health personnel available in floating hospital services surgery, several adjustments in anesthetic methods are required to rapidly return patients to their preoperative physiologic state. Therefore, we wrote this case report. Case Series: We presented case series of lower abdominal surgery performed in Ksatria Airlangga Floating Hospital with the implementation of peripheral nerve blocks as one of the ERAS protocols in one of the remote islands in Indonesia, Gili Iyang Island. Two patients underwent TAP blocks, while the remaining two received QL Blocks. A peripheral nerve block was performed under ultrasound guidance and a 20-mL injection of 0.25% levobupivacaine to QL muscle or TAP. During the observation, we found Visual Analogue Score (VAS) of 1-2 after surgery, no post-operative sedation needed, only 1 patient experienced nausea without vomiting, and the length of health facility stay were less than 3 days. Nearly all of our patients who underwent lower abdomen surgery got benefits from the application of peripheral nerve block. Because there was no opioid consumption in our cases, the risk of unwanted effect of opioids like postoperative nausea and vomiting, were also decreased. Conclusion: Peripheral nerve block, as mentioned TAP Block and QL Block, has emerged as a promising alternative to prevent and manage post-operative pain in remote medicine settings, namely Ksatria Airlangga Floating Hospital, particularly in areas with few medical facilities.